Impact of topographical factors and the land use and cover in the water quality of the basin of the Roseira stream, Jundiaí, São Paulo - Brazil - de Lima Andrade, Erik [UNESP]; de Faria, Carol Christina [UNESP]; Maia, Lauro Pessoa [UNESP]; Takikawa, Bruno Yuji [UNESP]; da Silva Manoel, Márcia Pereira [UNESP]; Ribeiro, Admilson Írio [UNESP]; de Medeiros, Gerson Araujo [UNESP] (Universidade Federal do Paraná, 2021)
The different forms of land use and cover, combined with the topography of a basin, modulate the occurrence and extent of erosion in water supply areas. This study aimed to examine the influence of topographic factors (slope and altimetry), combined with land use and land cover, on the turbidity of the Roseira Stream Basin, a sub-basin in the Jundiaí-Mirim River Basin, in the State of Sao Paulo, Brazil. According to the results, in general, most of the sampling points presented turbidity indexes above that stipulated in the law for Class I rivers, with the most downstream areas of the sub-basin being the most critical places with respect to this parameter. Pearson's linear correlation coefficients (r) and determination (R2) showed a negative correlation between turbidity and slope (R2 = 0.52). We concluded that disorderly urbanization in the flatter parts of the basin is a determining factor for the observed turbidity levels, despite the natural conditions of the basin in terms of topography and forest cover, indicating a restriction to the formation of runoff and sediment dragging.
Impacto dos fatores topográficos e do uso e cobertura da terra na qualidade das águas da bacia do córrego da Roseira, Jundiaí, São Paulo - Brasil
Keywords: Altimetry; Pearson correlation coefficient; Slope; Turbidity